Expression Analysis of Ribosomal Protein Genes, eL13 and eL14 in Nasopharyngeal Carcinoma Cell Lines - Wang, Phei-Lian; Sim, Edmund U. H. (UNIMAS Publisher, 2020)
Increasing evidence of the association between ribosomal protein (RP) genes with nasopharyngeal carcinoma (NPC) have been derived from findings of their differential expression patterns in NPC cell lines. Nevertheless, expression data from a comprehensive list of RP gene family members is still lacking. This paper reports the assessment of two RP genes, eL13 and eL14, with regards to their expression patterns in several NPC cell lines (TW04, TW01, HK1, HONE1 and SUNE-1) relative to a non-malignant control (NP69). A conventional Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) assay was employed. Analysis of eL13 has never been explored before this, whereas investigation of eL14 represents an extended study. We found a general over-expression trend of eL14 in 40% (2 of 5; TW01 and HONE-1) of the NPC cell lines studied, with higher upregulated level in only one (TW01) of them. However, this pattern of expression level is not statistically significant. Expression of eL13 was not detected in any of the cell lines used. The inconsistency of these expression patterns demonstrates an elusive nature of RP activities in the malignancy of the nasopharynx.